The synthesis and biological evaluation of Mycobacterium tuberculosis associated glycan derivatives - Bourke, Jean (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Mycobacterium tuberculosis establishes chronic infection and causes disease through manipulation of the host's innate and adaptive immune response. The bacterial cell wall is highly complex and contains a rich variety of glycosylated compounds, some of which are secreted during infection and have been proposed as immunomodulatory molecules. Amongst the most important of these are the p-hydroxybenzoic acid derivatives (p-HBADs) and phenolic glycolipids (PGLs). Herein is reported a synthetic methodology for the synthesis of these important biomolecules and their unnatural analogues and also the first in vitro study of the immunomodulatory effects of p-HBADs in isolation from the host bacterium.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin